Crack path and fracture surface analysis of ultrasonic fatigue testing under multiaxial loadings. (December 2022) - Reis, Luís; Da Costa, Pedro R.; Pereira, Ricardo; Montalvão, Diogo; Freitas, Manuel
Highlight: Cruciform specimens fatigue testing in ultrasonic fatigue machine. Tension-torsion specimens with different shear/axial stress biaxialities tested in ultrasonic fatigue. Higher shear/axial stress biaxiality present higher crack initiation angles. Different fatigue fracture surface features were identified in ultrasonic conditions. Abstract: Ultrasonic fatigue testing machines and related research are continuously growing. They allow researchers to study fatigue in a time and energy reliable manner, fatigue strength and fracture mechanics between 10E06 to 10E10 cycles, the established Very High Cycle Fatigue (VHCF) regime. Almost all published research to date was conducted under uniaxial tension–compression, pure torsion or bending loading under ultrasonic fatigue testing. The interest in multiaxial ultrasonic testing for VHCF has begun to evolve from the increasing available knowledge surrounding uniaxial fatigue in VHCF. Tension-Torsion and in-plane biaxial ultrasonic fatigue tests were first reached by adapting the tension–compression ultrasonic setup. The present work focuses on the crack path, critical initiation angle, fracture surface analysis and evaluation of different specimens, that failed under different biaxial loading conditions under ultrasonic fatigue. Specimens were specially designed and machined to function under ultrasonic fatigue machines resonance concept. Three different biaxial loading paths were carried out, in-phase tension–torsion and tension–tension, and out-of-phase tension–compression. Crack initiation, crack path and crack surface morphologies were analyzed by optic microscope and scanning electron microscope. Experimental results were analyzed and discussed; conclusions concerning these types of failures under ultrasonic testing regime are drawn.